Toleransi Beragama dan Persepsi Nilai Agama Pada Mahasiswa FISIP Universitas Sam Ratulangi - Fernanda Amny Syaputra; Lidya Ivana Rawung; Sintia Maria Rawis; Zuci Rahmani Zainal; Suhendra Abd Kader; Jegiftha Victoria Putri Pratami Lumettu; Madinatul Munawwarah Ridwan; Thessalonica S.F. Supit; Irfandi Pratama (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This study aims to determine the level of religious tolerance and perceptions of religious values, as well as to analyze the relationship between perceptions of religious values and religious tolerance among students of the Faculty of Social and Political Sciences, Sam Ratulangi University. The study employed a quantitative approach using descriptive and correlational methods. Data were collected through questionnaires distributed to 120 active students selected using a simple random sampling technique. The research instrument used a Likert scale and was analyzed using the Statistical Package for Social Science (SPSS). Data analysis techniques included descriptive analysis, validity testing, reliability testing, and Pearson Product-Moment correlation analysis. The results showed that students demonstrated a good level of religious tolerance and positive perceptions of religious values in social life. Correlation analysis also revealed a positive relationship between perceptions of religious values and students’ religious tolerance. The more positive the students’ perceptions of religious values, the higher their level of religious tolerance. This study concludes that religious values understood inclusively play an important role in fostering harmonious and mutually respectful social relationships within a multicultural campus environment.